(untitled) (Biological Sciences - PJSIR, 2001)
Brown seaweed species Cystoseira barbata, Jyengaria stellata and Sargassum boveanum were collected from Karachi coast at Ras Mauri (Capemonze) and Bulleji. Studies have been carried out to determine their fat content and the effect of weed S. boveanum diet on the cholesterol level of rabbit serum. To estimate the extent of the effectiveness of seaweed, a parallel study was made with a drug "LOPID" [gemfibroxil; 2, 2-dimethyl-5- (2, 5-Xylyloxy) Valerie acid; (Parke-Davis Corp.)]. The tested seaweed is more effective than the standard drug used.